The Stone Age of Qeqertarsuup Tunua (Disko Bugt) (Vol. 336):A regional analysis of the Saqqaq and Dorset cultures of Central West Greenland - Jens Fog Jensen (Monographs on Greenland | Meddelelser om Grønland, 2006)
suupTunua, however the archaeological evidence for such a development has yet to be found. When the cultural history of Qeqertarsuup Tunua is compared with that of Peary Land, the dwellingtypes and chronological units appear very similar. In the case of Dorset and Independence II, thesimilarities also extend to include the lithic inventory. As a consequence it is difficult to maintain adivision between Dorset in Western and Southern Greenland and Independence II in the HighArctic.